KERUSAKAN DAERAH ALIRAN SUNGAI DAN PENURUNAN DAYA DUKUNG SUMBERDAYA AIR DI PULAU JAWA SERTA UPAYA PENANGANANNYA - Mawardi, Ikhwanuddin (Jurnal Hidrosfir Indonesia, 2010)
Degradation and critical condition of watersheds in Java is showed by the damage of environmental condition, such as vegetation covered area that is less than 20%, big fluctuation of the river debit, frequent floods, land sliding and draught that its frequency is increased every year. These all result in the decrease of water resource capacity in Java. Besides, Java, that is only 7% of the area of Indonesia, has the highest population amongst islands in Indonesia and supplies the largest Indonesian economy (60%), needs continuously increase water resource capacity. Efforts to manage water resource through watershed environment rehabilitation, using functional approach (organizational roles) or structural approach likes physical/building rehabilitation is crucial to be carried out especially for the very critical watershed.